On the exponential growth of some multidimensional stable densities - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Б. Калинаускайте. О показательном убывании некоторых мноомерных устойчивых плотностей N. Kalinauskaitė. Daugiamačių stabilių tankių eksponentinio gesimo klausimu